Daya Hambat Ekstrak Buah Mahkota Dewa (Phaleria macrocarpa L.) Dengan Pelarut Ethanol dan Aquades Terhadap Bakteri Staphylococcus Aureus Penyebab Mastitis pada Sapi Perah - Wina Astriyani; Puguh Surjowardojo; Tri Eko Susilorini (TERNAK TROPIKA Journal of Tropical Animal Production, 2017)
The purpose of this research was determined effect of inhibitory the Phaleria macrocarpa  L. fruits extract with ethanol and aquades solvents againts Staphylococcus aureus. Materials used was Staphylococcus aureus which isolated from mastitis milk. Phaleria macrocarpa  L. fruits powder were extracted using ethanol and aquades with concentration were 10%, 20%, 30% and 40%. Iodips was used as control. Inhibitory of bacteria effect test was done by well diffusion methods. Variable was inhibition zone of each concentration, both of ethanol and aquades solvent. Data was analyzed by using two way nested ANOVA and continued by Duncan Multiple Range Test (DMRT). Result showed that highly significantly (P<0.01) on inhibition zone of Staphylococcus aures. Diameters of inhibitory was the optimum inhibition with ethanol solvent (17.46±0.67)mm and aquades solvent (11.14±0.30) mm. The best of  treatment of  Phaleria macrocarpa  L. fruits extract againts Staphylococcus aureus with ethanol and aquades solvent was 40%. The conclusion of this research is that mahkota dewa (Phaleria macrocarpa  L.) fruits extract with ethanol and aquades solvent in concentration 40% had a high ability to inhibit the growth of Staphylococcus aureus. Phaleria macrocarpa  L. fruits extract with ethanol higher in inhibiting capability the Staphylococcus aureus bacteria compared to aquades solvent.